Evaluating Global Oil Data Reporting Consistency and Stability with Insights from Indonesia - Taufik Roni Sahroni; Lulut Alfaris; Siagian, Ruben Cornelius; Andri Wahyudi; Anas Noor Firdaus; Ukta Indra Nyuswantoro (Scientific Contributions Oil and Gas, 2026)
Transparent and consistent oil data reporting is a critical component of global energy governance and market stability. This study evaluates the consistency, stability, and overall quality of global oil data reporting from 2002 to 2025 using the dataset of the Joint Organizations Data Initiative (JODI), with Indonesia employed as a regional reference case. The principal indicators applied include the Index of Reporting Consistency (IRC), the Reporting Volatility Index (RVI), and the Oil Data Availability Index (ODAI). Countries are classified according to market role (producer or importer), economic grouping, and geographical region. The analysis further incorporates K-means clustering and structural change detection to assess temporal stability and responsiveness to major global shocks. The findings reveal substantial variation in reporting performance across countries. Nations exhibiting high IRC values and low RVI scores generally possess more mature institutional and statistical capacities, whereas those with low IRC scores tend to face governance or data management constraints. Oil-producing countries typically demonstrate higher ODAI values but display greater vulnerability to systemic crises, while importing countries show relatively more stable reporting patterns. Major global shocks in 2008, 2014, 2020, and 2022 exerted asymmetric impacts on producers and importers, highlighting structural vulnerabilities within the global energy reporting system. Indonesia demonstrates consistently strong reporting performance, with an ODAI value of 0.944, exceeding the averages of ASEAN (0.889) and OPEC (0.829). The country records a non-reporting rate of only 5.6% and a maximum non-reporting duration of ten months. This study addresses a gap in long-term, shock-sensitive analyses and introduces an integrated framework combining IRC, RVI, and ODAI as a novel approach for assessing oil data reporting quality. The findings provide a foundation for strengthening institutional capacity, enhancing regional coordination, and developing crisis-resilient reporting systems, while positioning ODAI as a practical indicator for evaluating energy governance and policy transparency.